2007
DOI: 10.1007/s11095-007-9288-2
|View full text |Cite
|
Sign up to set email alerts
|

Melittin as an Epithelial Permeability Enhancer I: Investigation of Its Mechanism of Action in Caco-2 Monolayers

Abstract: Apically-added melittin opens tight junctions, causing dramatic TER reductions with significant increases in flux of dextrans. These effects appear mediated in part via PLA2 and involve alterations in specific tight junction proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 49 publications
4
28
0
Order By: Relevance
“…The increased lytic effects of melittin over conventional cationic antimicrobial peptides results from a higher hydrophobicity (17). Although the use of this antimicrobial peptide in the treatment of systemic infections is not feasible due to interaction with eukaryotic plasma membranes (9,15) at concentrations equivalent to antimicrobial activity, melittin has demonstrated potent ability to enhance the absorption of a range of molecules, including macromolecules in Caco-2 monolayers with minimal cytotox- 10.1007/s11095-007-9246-z icity in the polarized target cells (18)(19)(20). Melittin resulted in a rapid concentration-dependant decrease and subsequent recovery in TER in Caco-2 monolayers (20) with 1000-fold greater potency than that of C10 (5,21).…”
Section: Introductionmentioning
confidence: 99%
“…The increased lytic effects of melittin over conventional cationic antimicrobial peptides results from a higher hydrophobicity (17). Although the use of this antimicrobial peptide in the treatment of systemic infections is not feasible due to interaction with eukaryotic plasma membranes (9,15) at concentrations equivalent to antimicrobial activity, melittin has demonstrated potent ability to enhance the absorption of a range of molecules, including macromolecules in Caco-2 monolayers with minimal cytotox- 10.1007/s11095-007-9246-z icity in the polarized target cells (18)(19)(20). Melittin resulted in a rapid concentration-dependant decrease and subsequent recovery in TER in Caco-2 monolayers (20) with 1000-fold greater potency than that of C10 (5,21).…”
Section: Introductionmentioning
confidence: 99%
“…Andersson et al [44] proved that the rigidity of membrane can have considerable effect on melittin-membrane interaction. The apically added melittin can cause transepithelial electrical resistance reductions on dectrans flux [45]. Another study reported [46] that although amino acid sequence of Japanese frogs has similarity with that of melittin, their evolutionary relationship is not orthologous.…”
Section: Discussionmentioning
confidence: 99%
“…Cleavage of E-cadherin likely provokes loss of epithelial cell-cell contacts and may contribute to the genesis of eczematous dermatitis (41). Thus, an explanation retrospectively emerges for the recent finding that melittin enhances permeability of CaCo-2 epithelial cell monolayers (60). ADAM17 cleaves a large number of substrates including cytokines (e.g.…”
Section: Discussionmentioning
confidence: 99%